Sistem pilihan raya Malaysia: strategi dan penyelesaian - Mohamed Noor, Mohamed Amin (2024)
For countries that practice democracy, voting in elections is important to connect the people with the political system. In Malaysia, Suruhanjaya Pilihan Raya (SPR) plays an important role in ensuring that elections are fair, transparent, and systematic. Referring to the concept of fair and clean conduct, SPR needs to ensure and take into account that all election procedures and laws are carried out accurately, fairly, and thoroughly. In addition, the election procedure used should be consistent, and clear. Therefore, this study aims to examine the current methods used by the SPR in managing elections. In particular, this study also examines the strategies used by the SPR to ensure that the election system is fair, transparent and systematic. In addition, the study also suggests improvements that can be proposed to the SPR to achieve fair, transparent and systematic elections. Using a qualitative approach, 13 informants were selected, consisting of SPR officers and voters. Findings show that the SPR still has weaknesses in managing elections fairly, transparently, and systematically. The survey found that no significant changes were made in the election process by SPR. The study also highlighted the existence of corruption or money politics that have caused imbalances in the electoral system in Malaysia. This is evidenced when every time ahead of the election, national wealth is distributed to certain groups on the grounds that they care about the interests of a particular race. As a result, there are practices of cronyism, nepotism and money politics that have become a culture in elections in Malaysia. Because of that, this study looks comprehensively at what still causes elections in Malaysia to still need improvement, especially for the SPR. To ensure a fair, transparent and systematic electoral system, it is important to strictly monitor and control the politics of money. This includes setting contribution limits, disclosing the source of the contribution, and ensuring compliance with relevant laws. Transparency and accountability in political financing are essential to ensure that the electoral process is fair and free from undue influence.